Preparation and application of polyphenol nano-liposome loaded i-PRF skin dressing
By introducing polyphenol nanoliposome-loaded i-PRF skin dressings into the hydrogel, the problems of insufficient self-healing ability, poor biocompatibility and difficulty in inhibiting inflammation are solved, and a new hydrogel dressing with high biocompatibility, self-healing ability and anti-inflammatory effects are achieved, which promotes wound healing.
Patent Information
- Application Number
- CN202510199101.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-21
AI Technical Summary
Existing hydrogel dressings lack self-repair ability, poor biocompatibility and difficulty in solving the inflammatory microenvironment of wounds, limiting their widespread use in clinical applications.
Using polyphenol nanoliposome-loaded i-PRF skin dressing, a new hydrogel dressing with self-healing properties, excellent biocompatibility and anti-inflammatory ability was constructed by introducing oxidized sodium alginate, carboxymethyl chitosan, lyophilized concentrated growth factor and olive leucoside nanoliposomes into the hydrogel.
It improves the biocompatibility and self-healing ability of the hydrogel, significantly promotes cell growth and differentiation, reduces inflammatory response, enhances the mechanical properties and stability of the dressing, achieves a continuous drug-sustaining effect, and promotes wound healing.
Smart Images

Figure CN119656370A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of skin dressings, and in particular relates to the preparation and application of a skin dressing of polyphenol nanoliposome loaded with i-PRF. Background Art
[0002] The human body is a complex system composed of various organs and tissues. Among them, the skin, as the largest organ, has multiple functions such as protection, temperature regulation, sensation, metabolism, etc. The health of the skin directly affects our quality of life. However, skin defects are an easily overlooked problem, which may bring a series of hazards and pose a threat to our physical health. When our skin is injured, we need a fast, effective and safe dressing to help the wound heal. Hydrogel skin dressings, as an innovative wound care product, have become a leader in the field of wound treatment with its excellent moisturizing properties, good biocompatibility and superior anti-inflammatory properties. The working principle of hydrogel skin dressings is closely related to its unique physical properties. Hydrogel is a polymer network structure that can absorb and retain a large amount of water. This enables hydrogel skin dressings to provide a moist environment for the wound, which helps to maintain the activity and growth of wound cells. In addition, hydrogel dressings also have good oxygen permeability, allowing the wound to exchange gas normally, further promoting the healing process of the wound.
[0003] However, existing hydrogel dressings still have the following problems, which limit their further clinical application: 1) No self-healing ability: In the field of medical and biomaterials, hydrogel dressings are widely used due to their excellent hydrophilicity, biocompatibility and softness. However, traditional hydrogel dressings have a significant shortcoming, which is the lack of self-healing ability. As a wound dressing, traditional hydrogel materials are often difficult to restore their original structure and function in the face of sharp scrapes, strong impacts or severe chemical corrosion. This limitation of traditional hydrogel dressings has brought many inconveniences to practical applications. For example, in the medical field, when patients are traumatized, traditional hydrogel dressings are easily damaged after being scratched or hit by sharp objects, which not only reduces the protective effect of the dressing, but also may increase the risk of infection. In addition, in a chemically corrosive environment, hydrogel materials may degrade, causing them to lose their original properties, thereby affecting the treatment effect.
[0004] 2) Poor biocompatibility: The degradation rate and degree of hydrogel materials in vivo are key indicators for measuring their biocompatibility. Currently, a large number of hydrogel products have deficiencies in biodegradability, and their accumulation in the body often stimulates inflammatory responses, leading to a series of biocompatibility issues. Unfortunately, some existing hydrogel materials have poor cell adhesion, which limits their effectiveness in promoting cell growth and proliferation, and urgently need to be optimized and improved in the material design and preparation process.
[0005] 3) It is difficult to solve the inflammatory microenvironment of the wound: In the process of healing inflammatory wounds, the core goal is to effectively curb the rampant inflammatory response. Unfortunately, traditional hydrogels ignore the inclusion of potent anti-inflammatory factors in their formulations. Hydrogels lacking anti-inflammatory factors may not be able to suppress inflammation in biological tissue repair, affecting the repair effect. The introduction of anti-inflammatory factors can reduce inflammation and promote tissue repair. Hydrogels that ignore anti-inflammatory factors may also aggravate local immune responses and affect stability. Long-term use may also cause chronic inflammation and complications, affecting efficacy.
[0006] Therefore, it is necessary to develop a skin dressing with excellent anti-inflammatory ability, self-healing performance and good biocompatibility, which has broad application prospects in the field of skin wound healing and can bring patients a more reliable and comfortable use experience.
[0007] Oxidized sodium alginate and carboxymethyl chitosan both have good biocompatibility, which makes oxidized sodium alginate / carboxymethyl chitosan self-healing hydrogel have broad application prospects in the biomedical field. It can be used as a cell carrier in the fields of tissue engineering and drug delivery. However, the biggest advantage of oxidized sodium alginate / carboxymethyl chitosan self-healing hydrogel lies in its self-healing property. The aldehyde group of carboxymethyl chitosan can react with the amino group of oxidized sodium alginate to form a reversible covalent bond to form a hydrogel with self-healing function. When the hydrogel is damaged, the damaged part can quickly restore its original structure and function through the recombination of intermolecular forces. This self-healing property makes the hydrogel have higher stability and durability during the application process. However, during the degradation process of oxidized sodium alginate / carboxymethyl chitosan self-healing hydrogel in the body, some degradation products will be produced. These degradation products may have certain effects on the organism, such as causing inflammatory reactions, allergic reactions, etc.
[0008] In recent years, platelet concentrates, as an advanced tool for tissue regeneration, can effectively stimulate the regenerative potential of autologous tissues in the process of releasing growth factors beyond the conventional physiological dose. In this context, injectable platelet-rich fibrin (i-PRF) has attracted much attention. It is rich in many key growth factors, including but not limited to platelet-derived growth factor (PDGF), transforming growth factor β (TGF-β), insulin-like growth factor (IGF), etc. The introduction of i-PRF into the hydrogel matrix can not only significantly promote cell adhesion, proliferation and differentiation, but also greatly improve the biocompatibility of the hydrogel, providing an ideal growth environment for cells. In addition, the fibrinogen contained in i-PRF further enhances the mechanical properties of the hydrogel, ensuring that it exhibits excellent stability and durability when carrying cells or drugs. More importantly, the hydrogel incorporating i-PRF exhibits excellent biocompatibility in vivo, and its characteristics avoid the occurrence of inflammatory reactions. This advantage is due to the rich platelets and growth factors in i-PRF, which work synergistically to effectively promote cell proliferation and angiogenesis, thus facilitating the seamless integration of hydrogels with biological tissues. However, it is worth noting that the anti-inflammatory therapeutic effect of i-PRF is not static, and its efficacy stability is affected by many factors, including individual differences in patients, types of diseases, etc. These factors may lead to fluctuations in the treatment effect, thus requiring a more optimized treatment plan in clinical applications. Summary of the invention
[0009] The purpose of the embodiments of the present invention is to provide a preparation and application of a skin dressing containing polyphenol nanoliposomes loaded with i-PRF, aiming to solve the problems raised in the above-mentioned background technology.
[0010] The embodiment of the present invention is implemented as follows: a polyphenol nanoliposome-loaded i-PRF skin dressing comprises oxidized sodium alginate, carboxymethyl chitosan, freeze-dried concentrated growth factor and oleuropein nanoliposomes, wherein the concentration of oxidized sodium alginate is 0.2-0.5 g / ml, the concentration of carboxymethyl chitosan is 0.2-0.5 g / ml, the concentration of freeze-dried concentrated growth factor is 0.05-0.1 g / ml, and the concentration of oleuropein nanoliposomes is 0.125-1 ml / g (i.e., each gram of skin dressing contains 0.125-1 ml of oleuropein nanoliposomes).
[0011] Another object of the embodiment of the present invention is to provide a method for preparing a polyphenol nanoliposome-loaded i-PRF skin dressing, based on the above-mentioned polyphenol nanoliposome-loaded i-PRF skin dressing, comprising the following steps: Step 1: preparing oxidized sodium alginate, carboxymethyl chitosan, freeze-dried concentrated growth factor and oleuropein nanoliposomes respectively; Step 2: mixing oxidized sodium alginate and carboxymethyl chitosan, the two undergo a Schiff base reaction, and self-crosslink to form a first mixture, and the obtained skin dressing is recorded as sample S; Step 3: mixing the first mixture with the freeze-dried concentrated growth factor to obtain a second mixture, and the obtained skin dressing is recorded as sample SP; Step 4: Mix the second mixture with oleuropein nanoliposomes to obtain a third mixture, and the obtained skin dressing is recorded as sample SPO.
[0012] A further technical solution is that in step 1, the preparation method of the oleuropein nanoliposome is: Weigh phospholipids and cholesterol in a mass ratio of 4:1 to 20:1, and the sum of the mass of phospholipids and cholesterol is recorded as M1; weigh an appropriate amount of oleuropein, and record the mass as M2, so that M1:M2=(25-100):1. Add 10-30 times of anhydrous ethanol to the weighed phospholipids, cholesterol and oleuropein, and ultrasonicate for 5-10 minutes to completely dissolve them to obtain the oil phase, and then stir the PBS solution (phosphate buffered saline, Phosphate Buffered Saline) 4-6 times the oil phase with a magnetic stirrer into a vortex, and add the oil phase to the vortex PBS solution at a speed of 1 mL / min with a 5 mL syringe. After hydration for a period of time until the ethanol is evaporated and removed, filter it three times with 0.45 μm and 0.22 μm microporous filter membranes respectively, and finally obtain oleuropein nanoliposomes.
[0013] A further technical solution is that in step 1, the preparation method of oxidized sodium alginate is: Weigh 1 g of sodium alginate (SA) powder and dissolve it in 100 mL of deionized water. Then add 1.08 g of sodium periodate to the SA solution and react for 5 h in the dark. Add 1.5 mL of ethylene glycol and react for 1 h to neutralize the unreacted sodium periodate. Use a dialysis bag (molecular weight cutoff, 3500 Da) for dialyzing for 3 days. After freeze-drying, white flocculent oxidized sodium alginate (OSA) is obtained.
[0014] A further technical solution is that in step 1, the preparation method of the freeze-dried concentrated growth factor is: Autologous venous blood is collected for differential centrifugation, and the middle transparent layer is concentrated growth factor, which is freeze-dried for 24-48 hours at a freeze-drying temperature of -80°C to -90°C to finally obtain freeze-dried concentrated growth factor.
[0015] Another purpose of the embodiment of the present invention is to use a skin dressing of polyphenol nanoliposomes loaded with i-PRF, and to use the skin dressing prepared by the above method in the preparation of a pharmaceutical product for promoting skin wound healing.
[0016] The preparation and application of a skin dressing containing polyphenol nanoliposomes loaded with i-PRF provided in an embodiment of the present invention has the following beneficial effects: (1) Improving the biocompatibility of hydrogels: The prepared skin dressing can promote cell attachment and proliferation through the various growth factors and cytokines rich in i-PRF. When i-PRF is combined with hydrogels, these bioactive molecules can effectively promote cell growth and differentiation, thereby improving the biocompatibility of hydrogels. In addition, components such as fibrinogen and fibronectin in i-PRF can enhance the mechanical properties of hydrogels, making them more stable in the in vivo environment. Secondly, the introduction of i-PRF can also regulate the surface properties of hydrogels, making them more hydrophilic, thereby reducing inflammatory and rejection reactions. This improvement helps the hydrogel to better integrate with biological tissues and reduces the immune response caused by the material. In addition, the platelets in i-PRF can also release a variety of bioactive substances in the hydrogel, such as angiogenic factors and cell repair factors, which help accelerate the wound healing process and further improve the biocompatibility of hydrogels in clinical applications.
[0017] (2) A hydrophilic polyphenol sustained-release system was constructed (sustained release of hydrophilic polyphenol was achieved): Oleuropein nanoliposomes modified by ethanol injection method are hydrophilic and have high stability, good compatibility, good absorption effect and high bioavailability. The nanoliposomes were embedded in a hydrogel system composed of oxidized sodium alginate and carboxymethyl chitosan, thereby developing a new type of self-repairing skin dressing loaded with polyphenol nanoliposomes. First, the hydrogel has a porous three-dimensional network structure, which facilitates the diffusion of drug molecules and also provides a barrier to protect the drug from damage by the external environment. Second, the bilayer membrane structure of the liposome is semipermeable, and the release rate of oleuropein can be regulated according to the difference in the internal and external environment of the liposome. In the hydrogel, oleuropein is gradually released through the diffusion of the liposome bilayer membrane, achieving a sustained release effect of the drug. The dressing exhibits a sustained drug release characteristic and performs outstandingly in promoting wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the TEM electron microscope image of oleuropein nanoliposomes; Figure 2 Fourier transform infrared images of oxidized sodium alginate (OSA) and carboxymethyl chitosan (CMCS), as well as Fourier transform infrared images of sample S, sample SP and sample SPO synthesized based on the two; Figure 3 The SEM images of skin dressing samples S, SP and SPO; Figure 4Schematic diagram of the self-healing performance of skin dressing sample S; Figure 5 This is a diagram showing the results of a CCK-8 experiment of skin dressings in fibroblasts; Figure 6 Immunofluorescence detection of skin dressings for the expression of pro- and anti-inflammatory cytokines; Figure 7 Immunofluorescence images of PCR detection of pro- and anti-inflammatory cytokines in a cellular inflammation model; Figure 8 This is a bar graph showing the expression of pro-inflammatory and anti-inflammatory cytokines in the cell inflammation model detected by PCR; Fig. 9 The figure is the flow cytometry result of the expression of macrophage surface markers in the chronic inflammatory stage of cells in vitro by skin dressing; Fig.10 The antioxidant properties of skin dressings were evaluated by monitoring the level of reactive oxygen species using the DCFH-DA probe; Fig.11 The results of cell scratch test for skin dressing; Fig.12 Cell migration rate for skin dressings; Fig.13 The expression of angiogenic factors HIF-1α and VEGF; Fig.14 Immunofluorescence results of VEGF, CD31 and a-SMA; Fig.15 Skin dressings promote skin wound healing; Fig.16 Schematic diagram of the wound healing process for all groups; Fig.17 is the wound healing rate of all groups; Fig.18 In vivo biosafety evaluation of skin dressings. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0020] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0021] An embodiment of the present invention provides a polyphenol nanoliposome-loaded i-PRF skin dressing, comprising oxidized sodium alginate, carboxymethyl chitosan, freeze-dried concentrated growth factor and oleuropein nanoliposomes. In the embodiment of the present invention, the concentration of oxidized sodium alginate is 0.2 g / ml, the concentration of carboxymethyl chitosan is 0.2 g / ml, the concentration of freeze-dried concentrated growth factor is 0.05 g / ml, and the concentration of oleuropein nanoliposomes is 0.125 ml / g (i.e., each gram of skin dressing contains 0.125 to 1 ml of oleuropein nanoliposomes); or, the concentration of oxidized sodium alginate is 0.5 g / ml, the concentration of carboxymethyl chitosan is 0.5 g / ml, the concentration of freeze-dried concentrated growth factor is 0.1 g / ml, and the concentration of oleuropein nanoliposome is 1 ml / g; Alternatively, the concentration of oxidized sodium alginate is 0.35 g / ml, the concentration of carboxymethyl chitosan is 0.35 g / ml, the concentration of freeze-dried concentrated growth factor is 0.075 g / ml, and the concentration of oleuropein nanoliposomes is 0.25 ml / g.
[0022] It is only necessary to ensure that the concentration of oxidized sodium alginate is between 0.2 and 0.5 g / ml, the concentration of carboxymethyl chitosan is between 0.2 and 0.5 g / ml, the concentration of freeze-dried concentrated growth factor is between 0.05 and 0.1 g / ml, and the concentration of oleuropein nanoliposome is between 0.125 and 1 ml / g.
[0023] Another embodiment of the present invention provides a method for preparing a polyphenol nanoliposome-loaded i-PRF skin dressing, based on the above-mentioned polyphenol nanoliposome-loaded i-PRF skin dressing, comprising the following steps: Step 1: preparing oxidized sodium alginate, carboxymethyl chitosan, freeze-dried concentrated growth factor and oleuropein nanoliposomes respectively; Step 2: mixing oxidized sodium alginate and carboxymethyl chitosan, the two undergo a Schiff base reaction, and self-crosslink to form a first mixture, and the obtained skin dressing is recorded as sample S; Step 3: mixing the first mixture with the freeze-dried concentrated growth factor to obtain a second mixture, and the obtained skin dressing is recorded as sample SP; Step 4: Mix the second mixture with oleuropein nanoliposomes to obtain a third mixture, and the obtained skin dressing is recorded as sample SPO.
[0024] In the embodiment of the present invention, the prepared skin dressing was subjected to vacuum freeze drying for 24 hours and gold spraying, and then placed in a SEM emission scanning electron microscope to observe the surface and interior of the stent, and a SEM micrograph was obtained as follows: Figure 3 shown.
[0025] The amino groups of methyl chitosan react to form dynamic imine bonds. When the hydrogel is subjected to external force and the imine bonds are broken, the imine bonds can be spontaneously regenerated by contacting the aldehyde group and the amino group, thereby achieving self-repair of the hydrogel. Figure 4As shown in the figure, the self-healing performance of sample S was tested through a macroscopic self-healing experiment. Sample S dyed with methyl orange and transparent sample S were spliced together. After being placed at room temperature for 5 minutes, the spliced sample S was picked up with tweezers. The splicing of the two samples S did not break, proving the self-healing performance of sample S. The boundary of the splicing of the two samples S became blurred and the dye penetrated, indicating that a chemical reaction occurred on the fracture interface of sample S, rather than simple adhesion, further proving that the skin dressing achieved self-healing.
[0026] like Figure 5 As shown (where Figure 5 A is the cell viability bar graph of the CCK-8 experiment. Figure 5 B is a fluorescence graph of cell viability). The CCK-8 experiment (a highly sensitive colorimetric kit for detecting cell proliferation and cytotoxicity, which indirectly reflects the number and viability of cells by measuring the activity of dehydrogenases in living cells and is widely used in biomedical research) showed that compared with the complete culture medium, the extracts of sample S, sample SP and sample SPO had no effect on the proliferation of 929 cells, indicating that the skin dressing does not contain obvious cytotoxic components.
[0027] As a preferred embodiment of the present invention, in step 1, the preparation method of oleuropein nanoliposomes is: Weigh phospholipids and cholesterol in a mass ratio of 4:1 to 20:1, and record the mass of phospholipids and cholesterol as M1; weigh an appropriate amount of oleuropein, record the mass as M2, and make M1:M2=(25-100):1. Add 10-30 times of anhydrous ethanol to the weighed phospholipids, cholesterol and oleuropein, and ultrasonicate for 5-10 minutes to completely dissolve them to obtain the oil phase, and then stir the PBS solution of 4-6 times the oil phase into a vortex with a magnetic stirrer, and add the oil phase to the vortex PBS solution at a speed of 1 mL / min with a 5 mL syringe. After hydration for a period of time until the ethanol evaporates and is removed, filter it three times with 0.45 μm and 0.22 μm microporous filter membranes respectively, and finally obtain oleuropein nanoliposomes, whose TEM electron microscope image is shown as follows Figure 1 shown.
[0028] As a preferred embodiment of the present invention, in step 1, the preparation method of oxidized sodium alginate is: Weigh 1 g of sodium alginate (SA) powder and dissolve it in 100 mL of deionized water. Then add 1.08 g of sodium periodate to the SA solution and react for 5 h in the dark. Add 1.5 mL of ethylene glycol and react for 1 h to neutralize the unreacted sodium periodate. Use a dialysis bag (molecular weight cutoff, 3500 Da) for dialyzing for 3 days. After freeze-drying, white flocculent oxidized sodium alginate (OSA) is obtained.
[0029] In the embodiment of the present invention, the prepared oxidized sodium alginate was freeze-dried for 24 hours and then ground into powder using a grinder. The oxidized sodium alginate powder was mixed with potassium bromide powder in proportion and then subjected to infrared testing. The Fourier infrared spectrum (FT-IR) of the oxidized sodium alginate was obtained by analysis. Figure 2 As shown (where Figure 2 A is the Fourier infrared image of OSA, CMCS and sample S, Figure 2 B is the Fourier transform infrared image of sample S, sample SP and sample SPO), OSA spectrum at 1735 cm −1 A new characteristic peak appeared at 1692 cm-1, which is the stretching vibration absorption peak of the aldehyde group, indicating that OSA was successfully prepared. −1 The stretching vibration absorption peak of the imine group appeared at 1412 cm −1 The amino absorption peak at 1735 cm −1 The aldehyde absorption peak at 147° disappeared, indicating that the amino groups on the CMCS molecular chain reacted with the aldehyde groups of OSA, and sample S was successfully prepared. The OSA aldehyde groups reacted with the CMCS amino groups to form dynamic imine bonds. When the hydrogel was subjected to external force and the imine bonds were broken, the aldehyde groups and amino groups could spontaneously react to regenerate the imine bonds through contact, thereby achieving self-repair of the hydrogel.
[0030] As a preferred embodiment of the present invention, in step 1, the preparation method of the freeze-dried concentrated growth factor is: Venous blood is collected for differential centrifugation, and the middle transparent layer is concentrated growth factor, which is freeze-dried for 24-48 hours at a freeze-drying temperature of -80°C to -90°C to finally obtain freeze-dried concentrated growth factor.
[0031] like Figure 6 As shown, the expression of cytokines associated with macrophage M1 and M2 types was measured by immunofluorescence at the protein level, which further confirmed the macrophage polarization. The immunofluorescence results of IL-1β, TNF-α, and IL-6 ( Figure 6 ) showed that when cells were stimulated by endotoxin, the protein expression of IL-1β, TNF-α, and IL-6 increased. The SP group had significantly fewer IL-1β, TNF-α, and IL-6 positive cells than the negative control group, and the SPO group had the lowest percentage of IL-1β, TNF-α, and IL-6 positive cells. Immunofluorescence test results ( Figure 6 ) further confirmed the anti-inflammatory effect of the hydrogel. Compared with the blank control group and the inflammation control group (the experimental group treated with lipopolysaccharide, i.e., LPS), the sample SPO could significantly induce an increase in the number of Arg-1, TGF-β, and IL-10 positive cells.
[0032] Immunofluorescence results of PCR detection of pro- and anti-inflammatory cytokines in cell inflammation models are as follows Figure 7 The expression of pro- and anti-inflammatory cytokines is shown in Figure 8 As shown in Figure 2, the shift in macrophage polarization from M1 phenotype to M2 phenotype will inhibit local overt immune responses to prevent inflammatory damage and promote regenerative potential to accelerate the healing process. Macrophages can be polarized into classically activated M1 with proinflammatory properties and selectively activated M2 with anti-inflammatory properties. Therefore, the regulation of their phenotype may affect the occurrence, development and resolution of inflammation. Macrophages are stimulated to produce a large number of proinflammatory and anti-inflammatory cytokines. M1 macrophages produce proinflammatory cytokines such as IL-1β, IL-6 and TNF-α. M2 macrophages secrete anti-inflammatory factors such as IL-10, Arg1 and TGF-β to inhibit inflammation and promote tissue remodeling and repair. In order to study the immunomodulatory effect of SPO group hydrogel on macrophage inflammatory response and polarization, the expression of macrophage inflammatory factors was detected by qRT-PCR. After LPS stimulation, the levels of three proinflammatory cytokines (IL-1β, IL-6 and TNF-α) in macrophages increased sharply, and sample SPO significantly inhibited the expression of proinflammatory cytokines. Compared with the inflammation control group and the S group, the sample SPO significantly increased the expression of intracellular anti-inflammatory factors IL-10, Arg-1, and TGF-β. The above results show that the sample SPO can effectively induce the transformation of M1 macrophages into M2 macrophages and regulate the immune response.
[0033] Flow cytometry results of macrophage surface marker expression during chronic inflammatory phase of skin dressing in vitro Fig. 9 As shown, according to Fig. 9 It can be seen that sample SPO can significantly promote the polarization of M1 macrophages to M2 macrophages.
[0034] Antioxidant properties of skin dressings using DCFH-DA probe to monitor reactive oxygen species levels Fig.10 As shown, compared with the blank control group and the inflammation group, the sample SPO effectively reduced the level of intracellular ROS (Reactive Oxygen Species), the number of positive cells was significantly reduced, and the ROS clearance rate of the SPO group was higher than that of the S group and the SP group.
[0035] In vitro angiogenesis ability of skin dressings Figure 11-Figure 14 As shown in the figure, since the high migration ability of endothelial cells is an important factor affecting the formation of new blood vessels, the migration ability of endothelial cells was evaluated. First, HUVEC cells were scratched, and then co-cultured with the extracts of different hydrogel groups, and the healing of the scratches was observed for two consecutive days. The results of the scratch experiment are shown in the figure. Fig.11As shown in the figure, at 12 h, 24 h, 36 h and 48 h after scratching, the cell migration of SP group and SPO group was faster than that of the control group. At 48 h, the cell migration rate of each group was control group (42.63±1.63%), S (69.02±0.45%), SP (77.15±3.21%), SPO (94.15±1.23). The scratch in SPO group was basically completely healed, and significant migration was observed compared with other groups.
[0036] Afterwards, the migration of cells in each group of hydrogels was quantitatively analyzed, and the cell migration rate and the distance of the scratch were calculated, such as Fig.11 As shown, at 48 h, the distance of cell scratches in the SPO group was smaller than that in other groups, indicating that the sample SPO can promote cell migration and promote the healing of scratches; Fig.12 The cell migration rate at 48h was as high as 94.15%, which was much higher than that of the control group, S group and SP group, with statistical difference (P<0.001).
[0037] The expression of angiogenic factors HIF-1α and VEGF Fig.13 As shown, the SPO components of the vascular factors HIF-1α and VEGF were significantly expressed, confirming the angiogenic ability of SPO hydrogel.
[0038] Immunofluorescence results of VEGF, CD31, and a-SMA are shown in Fig.14 As shown in the figure, the protein expression of VEGF, CD31, and a-SMA in the SPO group hydrogel was significantly higher than that in the control group; the protein expression in the SPO group was significantly higher than that in the S group and the SP group, further confirming the angiogenic function of the hydrogel.
[0039] In summary, the SPO group hydrogel can promote the proliferation and migration of endothelial cells, thereby promoting angiogenesis. In conclusion, the sample SPO is an ideal skin dressing that can promote angiogenesis when tissue repair is impaired.
[0040] Experimental results on skin dressings promoting skin wound healing Figure 15-17 As shown in the figure, skin dressings promote skin wound healing. Fig.15 As shown, on the 3rd day, a large amount of yellow pus was observed in the control group and the S group, a small amount of pus was observed in the SP group, and the wound in the SPO group was relatively clean, with only a slight redness of the surrounding skin. From the 3rd day to the 12th day, the wounds in each group showed obvious healing. Fig.16 A schematic diagram of the wound healing process for all groups is shown. Next, the wound healing was quantitatively analyzed by measuring the wound size and then calculating the wound healing rate as the evaluation criterion ( Fig.17). During the 12-day treatment period, the wound healing rate in the SPO group was the fastest. The wound closure rate in the SPO group was as high as 98.55% after 12 days of treatment, while that in the control group, S group, and SP group was 96.94%, 97.55%, and 98.18%, respectively.
[0041] In vivo biosafety evaluation in a 12-day animal model Fig.18 As shown in the figure, the biotoxicity of the hydrogels in the S group, SP group, and SPO group was further evaluated by H&E staining of the heart, liver, spleen, lung, and kidney. Tissue sections showed that there were no morphological and histological changes in the organs of the S group, SP group, SPO group, and control group. Therefore, the prepared hydrogels have good in vivo biosafety.
[0042] Therefore, the prepared skin dressing can be used for treating skin wounds.
[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A polyphenol nanoliposome-loaded i-PRF skin dressing, characterized in that: The invention comprises oxidized sodium alginate, carboxymethyl chitosan, freeze-dried concentrated growth factor and oleuropein nanoliposome, wherein the concentration of oxidized sodium alginate is 0.2-0.5 g / ml, the concentration of carboxymethyl chitosan is 0.2-0.5 g / ml, the concentration of freeze-dried concentrated growth factor is 0.05-0.1 g / ml and the concentration of oleuropein nanoliposome is 0.125-1 ml / g.
2. A method for preparing a polyphenol nanoliposome-loaded i-PRF skin dressing, based on the polyphenol nanoliposome-loaded i-PRF skin dressing according to claim 1, characterized in that: The following steps are involved: Step 1: preparing oxidized sodium alginate, carboxymethyl chitosan, freeze-dried concentrated growth factor and oleuropein nanoliposomes respectively; Step 2: mixing oxidized sodium alginate and carboxymethyl chitosan, the two undergo a Schiff base reaction, and self-crosslink to form a first mixture, and the obtained skin dressing is recorded as sample S; Step 3: mixing the first mixture with the freeze-dried concentrated growth factor to obtain a second mixture, and the obtained skin dressing is recorded as sample SP; Step 4: Mix the second mixture with oleuropein nanoliposomes to obtain a third mixture, and the obtained skin dressing is recorded as sample SPO.
3. The method for preparing the polyphenol nanoliposome-loaded i-PRF skin dressing according to claim 2, characterized in that: In step 1, the preparation method of the oleuropein nanoliposome is: Weigh phospholipids and cholesterol in a mass ratio of 4:1 to 20:1, and the sum of the masses of phospholipids and cholesterol is recorded as M1; weigh an appropriate amount of oleuropein, and record its mass as M2, so that M1:M2=(25-100):1; add 10-30 times of anhydrous ethanol to the weighed phospholipids, cholesterol and oleuropein, and ultrasonicate for 5-10 minutes to completely dissolve them to obtain an oil phase, and then stir a PBS solution of 4-6 times the oil phase into a vortex with a magnetic stirrer, add the oil phase to the vortex PBS solution with a 5mL syringe at a speed of 1mL / min, hydrate for a period of time until the ethanol is evaporated and removed, and filter it with 0.45μm and 0.22μm microporous filter membranes for 3 times respectively to finally obtain oleuropein nanoliposomes.
4. The method for preparing the polyphenol nanoliposome-loaded i-PRF skin dressing according to claim 2, characterized in that: In step 1, the preparation method of oxidized sodium alginate is: Weigh 1 g of sodium alginate powder and dissolve it in 100 mL of deionized water. Then add 1.08 g of sodium periodate to the SA solution and react for 5 h in a dark environment. Add 1.5 mL of ethylene glycol and react for 1 h to neutralize the unreacted sodium periodate. Use a dialysis bag for dialyzation for 3 days and freeze-dry to obtain white flocculent oxidized sodium alginate.
5. The method for preparing the polyphenol nanoliposome-loaded i-PRF skin dressing according to claim 2, characterized in that: In step 1, the preparation method of the freeze-dried concentrated growth factor is: Autologous venous blood is collected for differential centrifugation, and the middle transparent layer is concentrated growth factor, which is freeze-dried for 24-48 hours at a freeze-drying temperature of -80°C to -90°C to finally obtain freeze-dried concentrated growth factor.
6. An application of a skin dressing of i-PRF loaded with polyphenol nanoliposomes, the skin dressing prepared by the method for preparing a skin dressing of i-PRF loaded with polyphenol nanoliposomes according to any one of claims 2 to 5, characterized in that: The skin dressing is used in preparing a medical product for promoting the healing of skin wounds.
Citation Information
Patent Citations
Drug-loaded liposome hydrogel as well as preparation and application thereof
CN115887744A
Preparation method and application of A-PRF-loaded injectable temperature-sensitive hydrogel
CN117224473A
Preparation method of pH-responsive double-release hydrogel for promoting healing of diabetic wounds
CN118892573A
Composite hydrogel wound dressing
CN204379848U
Tissue substitute material with biologically active coating
US20150367032A1
Cited By
CGF-loaded hydrogel, preparation method and application in wound repair
CN120714095A